IXPE observation of PKS 2155–304 reveals the most highly polarized blazar - Kouch, Pouya M.; Liodakis, Ioannis; Middei, Riccardo; Kim, Dawoon E.; Tavecchio, Fabrizio; Marscher, Alan P.; Marshall, Herman L.; Ehlert, Steven R.; Di Gesu, Laura; Jorstad, Svetlana G.; Agudo, Iván; Madejski, Grzegorz M.; et al. (EDP Sciences, 2025)
We report the X-ray polarization properties of the high-synchrotron-peaked (HSP) blazar PKS 2155−304 based on observations with the Imaging X-ray Polarimetry Explorer (IXPE). We observed the source between Oct 27 and Nov 7, 2023. We also conducted an extensive contemporaneous multiwavelength (MW) campaign. We find that during the first half (T1) of the IXPE pointing, the source exhibited the highest X-ray polarization degree detected for an HSP blazar thus far, (30.7 ± 2.0)%; this dropped to (15.3 ± 2.1)% during the second half (T2). The X-ray polarization angle remained stable during the IXPE pointing at 129.4° ±1.8° and 125.4° ±3.9° during T1 and T2, respectively. Meanwhile, the optical polarization degree remained stable during the IXPE pointing, with average host-galaxy-corrected values of (4.3 ± 0.7)% and (3.8 ± 0.9)% during the T1 and T2, respectively. During the IXPE pointing, the optical polarization angle changed achromatically from ∼140° to ∼90° and back to ∼130°. Despite several attempts, we only detected (99.7% conf.) the radio polarization once (during T2, at 225.5 GHz): with degree (1.7 ± 0.4)% and angle 112.5° ±5.5°. The direction of the broad pc-scale jet is rather ambiguous and has been found to point to the east and south at different epochs; however, on larger scales (> 1.5 pc) the jet points toward the southeast (∼135°), similarly to all of the MW polarization angles. Moreover, the X-ray-to-optical polarization degree ratios of ∼7 and ∼4 during T1 and T2, respectively, are similar to previous IXPE results for several HSP blazars. These findings, combined with the lack of correlation of temporal variability between the MW polarization properties, agree with an energy-stratified shock-acceleration scenario in HSP blazars.